Effectiveness of Sleep Hygiene-Based Interventions on Sleep Quality in Hemodialysis Patients: A Systematic Review and Meta-Analysis - Jamiatun; Thika Marliana; Aprisunadi; Agung Tri Nugraha; Nurul Hidayah (Journal of Scientific Insights, 2026)
Background: Patients with Chronic Kidney Disease (CKD) undergoing hemodialysis frequently experience severe sleep disturbances, negatively impacting both physical and psychological health outcomes. Non-pharmacological interventions, such as sleep hygiene, are considered safer and more practical alternatives for improving sleep quality. However, the currently available evidence on sleep hygiene interventions in hemodialysis patients requires a comprehensive quantitative synthesis to establish clear practice guidelines. Objective: This systematic review and meta-analysis aimed to assess the clinical effectiveness of sleep hygiene-based interventions on sleep quality among individuals receiving maintenance hemodialysis. Methods: A systematic literature review and meta-analysis were conducted in accordance with the PRISMA 2020 guidelines. Electronic databases, including PubMed, Scopus, and Google Scholar, were searched for articles published between 2014 and 2026. Eligible studies included randomized controlled trials (RCTs) and quasi-experimental designs involving hemodialysis patients who received sleep hygiene interventions with reported quantitative outcomes on sleep quality. The risk of bias was evaluated using the Cochrane RoB 2 and JBI Critical Appraisal tools. Quantitative synthesis was performed using a random-effects model. Results: Out of 428 identified records, 8 studies met the strict inclusion criteria. Sleep hygiene-based interventions—including behavioral education, relaxation techniques, spiritual care, and cognitive-behavioral therapy for insomnia (CBT-I)—significantly improved sleep quality among hemodialysis patients. A meta-analysis of the studies demonstrated a large and highly significant pooled intervention effect size favoring sleep hygiene-based approaches (pooled Standardized Mean Difference, SMD = -1.20, 95% CI [-1.45, -0.95], p < 0.001). Most included studies reported substantial reductions in Pittsburgh Sleep Quality Index (PSQI) scores following intervention. Associated comorbid symptoms such as fatigue, anxiety, depression, and restless legs syndrome also showed concurrent significant improvements. Heterogeneity among the studies was moderate. Conclusion: Sleep hygiene-based interventions represent powerful, effective, safe, low-cost, and nurse-led non-pharmacological approaches to improving sleep quality in hemodialysis patients. These evidence-based strategies should be routinely integrated into independent nephrology nursing care plans. Future research employing larger, multicenter, methodologically rigorous RCTs is warranted to further confirm long-term clinical benefits.